Cognitive outcome and cyclo-oxygenase-2 gene (−765 G/C) variation in the preterm infant. Issue 2 (11th August 2006) - Harding, D R; Humphries, S E; Whitelaw, A; Marlow, N; Montgomery, H E
Abstract : Background: Cyclo-oxygenase (COX) inhibition by indomethacin does not result in an improvement in long-term neurocognitive outcome, despite reducing the incidence of both severe intraventricular haemorrhage and white matter injury visible on ultrasound. Diffuse brain injury after preterm birth may have inflammatory origins. These two points suggest that, in the preterm brain, COX inhibition may have a dominant proinflammatory or neuropathological role. The inducible form of the COX2 gene is polymorphic: the −765 C (rather than G) variant of the gene is associated with reduced COX2 activity. Objective: To test the hypothesis that the C allele of COX2 is associated with worse neurodevelopmental outcomes after premature birth. Outcomes: Cerebral palsy, disability, Griffith's developmental quotient at 2 years and British Ability Scales-11 general cognitive ability and motor performance (movement assessment battery for children) at 5½ years were compared with COX2 genotype. Results: The C allele (GC 65 (31%), CC 3 (1%)) was independently associated with worse cognitive performance at 2 and 5½ years: C allele mean (SEM) developmental quotient 92.7 (1.7), v GG 97.6 (1.5), p = 0.039; C allele mean (SEM) general cognitive ability, 94.3 (2.2) v GG 100.9 (1.7), p = 0.028. Conclusion: An antineuropathological role for COX2 in the preterm brain may help account for the lack of effect of indomethacin treatment in improving neurocognitive outcomes in children born preterm, despite reported reduction in apparent brain injury.